Suppression of Murine Lymphocyte Mitogen Responses by Exopolysaccharide from Capnocytophaga ochracea - Bolton, Ronald W. (1983)
An extracellular polysaccharide was purified from culture supernatants of Capnocytophaga ochracea 25, a gram-negative bacillus associated with human periodontal disease. The extracellular polysaccharide suppressed in vitro mitogenic responses of murine splenic lymphocytes to concanavalin A and lipopolysaccharide. This suppression wad dose dependent, persisted up to 120 h, and was not caused by direct toxicity of the extracellular polysaccharide.